Evaluation of nurses’ practices toward postoperative wound dressing in surgical wards - Atiyah, Hussein; Khudhur, Khalidah; hasan, Sadeq (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): The study aimed to assess the level of nursing performance and practices in terms of approaching or distancing itself from the optimal performance criteria universally adopted within the variable dressing surgical wounds of patients admitted to the surgical wards, and determine the relationship between the level of nurse’s performance and socio-demographic characteristics of them in those wards. Methodology: A descriptive assessing design was adopted from November the 10th, 2010 until June the 1st, 2011 to assess the nursing care provided practices for the postoperative period within the variable dressing surgical wounds in the complex of Medical City. Whereas the study was conducted in three hospitals; Baghdad Teaching Hospital, ALShahid Ghazi Hariri for surgical specialties, and nursing home hospital. A Purposive "non- probability" sample consisting of (55) nurses from those who working in surgical wards at the time of data collection. The data were collected after adapting AL-Ajloni questionnaire by the researchers that is dedicated to the purposes of the study and composed of two major parts; the first part includes the page of socio-demographic data which contains (6) paragraphs, and the second one includes the page of the major components of the study which contains (4) domains in (39) sub-domain. The validity of the questionnaire was determined by (7) experts in the specialty field. While, the reliability of the questionnaire was determined by calculating the correlation coefficient (Pearson), which was statistically acceptable value (r = 0.86). Data were collected through direct observant approach by the mean of the designed practice checklist. Thereafter, the data were analyzed through the application of descriptive analysis measures (frequencies and percentages), as well as weighted arithmetic mean and Pearson correlation coefficient by using (SPSS) Version 16. Results: The findings of the study indicated that academic nurses had performed adequate practices relative to postoperative wound dressing than practical ones. All nurses regardless of their gender had performed almost at the same level of practices relative to postoperative wound dressing. Older nurses demonstrated inadequate practices concerning postoperative wound infection precautions. The quality of nurse’s performance regarding postoperative dressing procedure was strong positive relationship with level of education. Nurses who had participated in training sessions performed the same practices of others without it. 29 Nurses’ practices and postoperative wound dressing Recommendations: standards practice guide lines should be available for every nurse in hospital; furthermore strict nosocomial infection control precaution should be followed by health care providers. In addition thorough advanced training courses should be available for nurses dedicated in its nature toward standards ideal safe practice